Optimizing Laparoscopic Surgery Outcomes: An Analysis of Risks and Complications in Resource-Constrained Environment: Addressing Challenges and Improving Safety in Low-Resource Surgical Settings - Piyush Tarwey; Rajesh Kumar Singh; Ritika Kedia; Khushboo saran; Dipali Singh; Jay Prakash (Student’s Journal of Health Research Africa, 2024)
Background: Laparoscopic surgery has enormous advantages over open surgery, the most important of which include decreased postoperative pain, shorter hospital stays, smaller incisions, and quicker recovery. Although laparoscopic surgery has been adopted widely, it continues to present challenges in resource-constrained conditions; that is, the limitation of available records related to surgery according to differing levels of expertise of surgeons sometimes causes great problems in outcome evaluation. This study was conducted to evaluate the incidence, nature, and risk factors for complications during laparoscopic surgery, particularly in a resource-constrained environment. Methods: This prospective observational study was conducted on 97 patients with different complaints undergoing elective laparoscopic cholecystectomy, appendicectomy, or herniorrhaphy. Patients’ demographics, comorbidities, and perioperative variables were collected and analyzed. Statistical analysis was done using the Chi-square test and logistic regression modelling for detecting significant associations, with a p-value of < 0.05 being statistically significant. Results: The overall complication rate was found to be 17.52%: Cholecystectomy, being the most common procedure (58.78%), had a 15.78% complication rate, whereas appendicectomy had the minimum incidence (3.33%) and herniorrhaphy, the maximum (60%). Risk factors found to be notable correspond with advanced age, hypertension, diabetes, and lesser experience (<4 years) by the surgeons. These risk factors tend to exhibit a strong positive correlation with high complication rates, particularly in cases of herniorrhaphy. Conclusion: The findings highlight the need for specifically targeted preoperative risk assessments, improved surgical education, and adherence to standardized procedures to reduce complications. Optimization of care strategies and resource allocation by enhancing relative outcomes for laparoscopic surgery can lead to future clinical and research gains in the resource-constrained environment.